Analysis of Problematic Credit Settlement: The Role of Notary in Resolving Nonperforming Loans through Collateral Acquisition - Vianney Bagus Raditya, Yohanes Mario; Sihabudin; Hendrarto Hadisuryo (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
This research is intended to analyze the credit agreement in the Indonesian banking sector can be done through authentic deeds or underhand deeds. The author uses Socio Legal Legal Research Methods or commonly used with the term empirical juridical research. Empirical legal research, namely data obtained directly from the community as the first source through field research . Credit agreements that are regulated through authentic deeds have the advantage of strong evidentiary power, because the authentic deed is made before a notary or authorized employee according to the law in the place where the deed is issued. On the other hand, agreements arranged through underhand deeds between banks and debtors still have legal validity but are not as strong as authentic deeds because they do not have authorization from authorized officials and are not supported by witness signatures. Concerning collateral in the form of a mortgage certificate, the making of which is carried out by a Land Deed Official (PPAT) and a mortgage certificate issued by the Land Office as proof of mortgage rights in accordance with Article 14 paragraph (1) of Law No. 4 of 1996. In the implementation of non-performing loan settlements, the role of notaries as authentic deed makers is very important. After the settlement of bad debts between banks and customers through an alternative settlement process, namely the Debtor's Juridical Agreement and the Debtor's Juridical Mandate (AYDA) to obtain strong evidence, it is necessary to make an authentic deed by a Notary. This is based on Article 1866 of the Civil Code which regulates evidence, which includes written evidence, evidence with witnesses, suspicion, recognition, and oaths. The findings and conclusions obtained by the researcher in the form of suggested changes in Article 12 Paragraph (1) of Law Number 10 of 1998 concerning Amendments to Law Number 7 of 1992 concerning Banking are the importance of replacing the phrase "commercial bank" with "every bank" to conform to the principles of the 1945 Constitution of the Republic of Indonesia. It is hoped that this change can provide equality in authority and freedom for all banks in taking over collateral through an auction process to resolve non-performing loans faced by these banks.